Re-centralization and the delivery of social security services - Cruz, Neil Angelo L. (2003)
The study is basically focused on how the new policy of the Social Security System (SSS) affects the delivery of service to its members. Over the years, SSS continued to provide meaningful protection to its members and their families in times of contngencies and crisi. Through it all, difficulties and challenges abound in its pursuit of excellence in the performance of its mandated principle. The study used the questionnaire-survey form, in which respondents were members from one of the many SSS branches in Negros Occidental. The chosen sample branch is the SSS Bago Branch and the members transacting within it. Said branch was chosen because of its status as one of the Receiving Center of SSS Bacolod Processing Center under the new set-up. Thirty (30 respondents/members including four (4) SSS personnel have been asked to give opinions, comments on the new re-centralization policy of the System and its effects on the delivery of service to its members.
[Research Paper (PM 299-Research Methods and applications). -- Iloilo City : UPV-CM, 3rd Trimester 2002-2003.